Quentin Meillassoux e a crítica ao correlacionismo - Bruno Domenico Nicolai Cecchini (2022)
Quentin Meillassoux's speculative materialism had an ample repercussion in the philosophical millieu in the first years of the 21st century, not the least for its ambition to reclaim 'metaphysical' thought in a 'post-metaphysical' context, but also for the ingeniousness of construing its enemy: Correlation, which basically designates the hegemony of post-kantian philosophies, formulating it as a diverse philosophical lineage, albeit united in its correlational essence. It is from the critique of correlational thought that Meillassoux constructs his metaphysical system. If the repercussion was ample, then no less ample were the plethora of critiques towards a rejection of his speculative materialism and his diagnosis concerning the staleness in which philosophy finds itself with the predominance of what he calls the correlation in post-kantian philosophies. This dissertation is intent on dealing with the critiques which fall either on Meillassoux's diagnostic or his philosophical project ─ both being intertwined. For this sake it will be made a conceptual unification of his philosophical system as a means to deal with the ambiguities identified as the origin of the critiques.